BMW: Stracer Study Analysis of Banking and Microfinance Skills Programs - Nurhayati, Tri; Rijanto, Tri; Novtiana, Rizcha (Jurnal Ilmu Sosial Mamangan, 2024)
This research aims to investigate and analyze the career paths of graduates of the Banking and Microfinance Skills Program at XYZ University through a tracer study approach. The main focus of this research is to evaluate the extent to which the BMWs (Fields of Interest and Competencies) acquired during the studies influence their professional careers as well as the relevance of the acquired competencies to the needs of the job market in the banking and microfinance sectors. A qualitative approach was used in this research, with structured in-depth interview techniques with graduates as the main data collection method. Interviews will focus on graduates' career experiences, how they apply the knowledge and skills obtained from the study program, as well as evaluation of their preparation in facing challenges and demands in the workplace. This research receives urgency due to changing dynamics in the banking and microfinance sectors which are increasingly complex and changing rapidly. By tracking graduates' career trajectories, this research will provide a deeper understanding of the extent to which higher education curricula can adapt to these changes as well as BMW's real contribution in preparing graduates for success in the world of work. It is hoped that the results of this research can provide valuable input for the development of educational programs, enable universities to increase the relevance of curricula to industry needs, and provide insight to prospective students regarding career prospects and skills required in the banking and microfinance sectors